Analysis of the study of consumer protection law against expired food products and medicines from a business law perspective - Marheni, Lily (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This research aims to provide a comprehensive examination of consumer protection against the circulation of expired food and pharmaceutical products through the lens of business law. Specifically, it seeks to explore the intricate relationship between consumer protection laws and business law, emphasizing the regulatory measures and ethical responsibilities of business actors. The study is grounded in legal frameworks such as Law No. 8 of 1999 on Consumer Protection, Law No. 18 of 2012 on Food, and various regulations issued by BPOM (Indonesian Food and Drug Authority). Employing a normative juridical approach, this research critically analyzes legislative provisions, regulatory implementation, and the accountability mechanisms imposed on business actors. Data collection relies on document analysis, focusing on primary and secondary legal materials such as statutes, government regulations, and official reports. The method enables an in-depth understanding of the challenges in the enforcement of consumer protection laws. The analysis reveals that while the legislative framework is robust and comprehensive, there are significant gaps in its practical application. Weak supervision, limited public awareness, and insufficient compliance among business actors hinder the realization of consumer protection goals. Furthermore, the ethical responsibilities of business entities often remain secondary to profit-oriented priorities, exacerbating the risks to consumer health and safety. The study concludes that strengthening regulatory oversight, enhancing ethical standards for business actors, and refining the legal framework are essential to safeguarding consumer rights. Improved coordination between regulatory authorities and consistent enforcement of penalties for non-compliance are critical to creating a safer and more transparent market environment. By promoting awareness and accountability, this research highlights the potential for a more effective balance between consumer interests and business practices.